2005
DOI: 10.1539/joh.47.143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mixed Organic Solvents on Neuromotor Functions among Workers in Buddhist Altar Manufacturing Factories

Abstract: Effects of Mixed Organic Solvents on Neuromotor Functions among Workers in BuddhistAltar Manufacturing Factories: Toyoto IWATA, et al. Department of Environmental Health Sciences, Akita University School of Medicine-To clarify the neuromotor effects of long-term exposure to mixed organic solvents, postural sway and tremor were measured in 62 solvent workers of four Buddhist altar manufacturing factories who had worked for 1-46 (mean 12) yr. By using the passive gas sampler, 8-h time-weighted average concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 19 publications
4
22
0
7
Order By: Relevance
“…Few studies investigated effects of chronic exposure to volatile organic solvents on balance control through posturography, which is now recognized as a useful technique to assess neurotoxic effects on CNS (Ledin et al 1991;Kuo et al 1996;Yokoyama et al 1997;Iwata et al 2005;Vouriot et al 2005b;Herpin et al 2008). While most studies have shown that chronic exposure close to or higher than workplace threshold limit values led to balance disorders, the additive neurotoxic effects after a weeklong exposure, defined here as subchronic, are, to our knowledge, less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies investigated effects of chronic exposure to volatile organic solvents on balance control through posturography, which is now recognized as a useful technique to assess neurotoxic effects on CNS (Ledin et al 1991;Kuo et al 1996;Yokoyama et al 1997;Iwata et al 2005;Vouriot et al 2005b;Herpin et al 2008). While most studies have shown that chronic exposure close to or higher than workplace threshold limit values led to balance disorders, the additive neurotoxic effects after a weeklong exposure, defined here as subchronic, are, to our knowledge, less understood.…”
Section: Introductionmentioning
confidence: 99%
“…36 Our results are in accordance with the conclusions of several previous studies [36][37][38] that postural balance testing has proven useful in identifying subtle neuromotor abnormalities secondary to exposures to jet fuel, solvents, alcohol and lead. Other studies [39][40][41][42] also concluded that posturography is a useful technique to assess the toxicity of solvents on the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Hand tremor was measured successively for each hand for 16.4 s, by asking the subjects to hold a light stylus, containing a biaxial micro-accelerometer, as he would hold an ordinary pen, with the elbow joint bent at a right angle and free of body contact or any obstacles (DesprĂ©s et al 2000;Iwata et al 2005bIwata et al , 2006Murata et al 2004;Nadeau et al 2003). The stylus was held horizontally, parallel to the abdomen at approximately 10 cm in front of the navel and the index Wnger was positioned about 1 cm from the tip of the stylus.…”
Section: Methodsmentioning
confidence: 99%